Verification of Data Resulting from Technical Surveillance by the Court - Andrei Apostol (EIRP Proceedings, 2019)
The present analysis aims to highlight the different methods of verification of the data obtained by judicial bodies through technical surveillance methods provided by the Criminal Procedure Code. Although the current legislative framework as interpreted by the Constitutional Court of Romania provides specific guarantees in order to prevent using forged evidences in the criminal trial, we believe that the court, after the indictment, needs to verify on its own the authenticity of such means of evidence. Therefore, the doctrine and the recent jurisprudence of national courts stated in this context the need for an independent expertise that can analyze the data obtained through technical surveillance in order to be used as evidence in a criminal trial. Also, the present context of the Romania legislative reform and the context in which several cooperation protocol between criminal investigation bodies and Romanian Intelligence Service were declassified, led to a stringent need for such an expertise. We tend to believe that without an independent expert that can assess whether the recordings are authentic or not, the court cannot in good faith decide to convict a person. Present paper is of interest to any law practitioner as it tries to highlight in a concise manner both the framework for such an expertise and the means to obtain it.